Optimizing glycemic control in type 2 diabetes: the impact of the GLIDE program’s personalized digital health intervention - Anand Ambesange; Amit Lala Khomane; Jaymin Parikh; Devina Aswal; Mihir Gharia; Prachi Sharma; Vishva Trivedi; Twinkle Maheshwari; Astha Mishra; Bhavan Bhavsar; Vrushali Athavale (Frontiers in Clinical Diabetes and Healthcare)
BackgroundThe integration of digital health applications into type 2 diabetes mellitus (T2DM) management presents promising opportunities for optimizing glycemic control, enhancing adherence, and improving health outcomes. MyTatva’s Glycemic Lifestyle Intervention in Diabetes Empowerment (GLIDE) program, which integrates dietary and exercise regimens, cognitive behavioral therapy (CBT), and Internet of Things (IoT) devices, potentiates this approach. This study aimed to evaluate the effectiveness of the GLIDE program’s personalized, comprehensive approach in improving glycemic control over 90 days among T2DM patients.MethodsDuring the study period, 30 diabetic patients completed their GLIDE journey with expert dieticians, physiotherapists, and behavior therapists. Each patient received a personalized root cause analysis based on lifestyle assessment and disease-specific parameters. Statistical analysis was conducted using a paired t-test on the deidentified HbA1c, FBS, and PPBS data at baseline and post-intervention.ResultsThroughout the study, 27 patients actively adhered to the GLIDE program. All the parameters showed statistically significant (p<0.05) changes post-intervention. HbA1c decreased by 11.79% from 8.43% ± 1.32 to 7.44% ± 0.64. Significant reductions were observed in PPBS (47.7%), decreasing from 260.89 mg/dL ± 36.31 to 136.27 mg/dL± 6.36, compared to FBS (31.1%), which decreased from 8.43 mg/dL± 1.32 to 7.44 mg/dL± 0.64.ConclusionsThe effectiveness of the GLIDE program is based on a comprehensive root cause analysis approach. The detailed analysis of the patient’s clinical journey by health experts at regular intervals enables precise goal management, resulting in expected outcomes for better glycemic control. Therefore, personalized digital health plans are vital for achieving clinically significant changes.